2005
DOI: 10.1002/ijc.21514
|View full text |Cite
|
Sign up to set email alerts
|

Chemokine receptors in head and neck cancer: Association with metastatic spread and regulation during chemotherapy

Abstract: Head and neck carcinomas are histologically and clinically heterogeneous. While squamous cell carcinomas (SCC) are characterized by lymphogenous spread, adenoid cystic carcinomas (ACC) disseminate preferentially hematogenously. To study cellular and molecular mechanisms of organ-specific metastasis, we used SCC and ACC cell lines and tumor tissues, obtained from patients with primary or metastatic disease. Comprehensive analysis at the mRNA and protein level of human chemokine receptors showed that SCC and ACC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
75
0
1

Year Published

2006
2006
2016
2016

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 92 publications
(83 citation statements)
references
References 53 publications
6
75
0
1
Order By: Relevance
“…Furthermore, given the elevated CXCL13 expression in the serum of patients with metastatic disease as compared with patients without evidence of tumour burden, this chemokine may also serve as a tumour marker. In our analysis of breast cancer cell lines and tumour samples, we found the expression of chemokine receptor CXCR5 to be restricted to the cytoplasma, a finding that is in line with observations of Muller et al (2006) who detected CXCR5 intracellulary but did not detect surface expression of CXCR5 in cell lines and tumour samples from patients with metastatic head and neck cancer. Although these findings, at first glance, do not support the concept of CXCR5 as the main target for CXCL13 overexpression in breast cancer, we believe that they do not reflect the potential role this chemokine receptor might play in vivo.…”
Section: Discussionsupporting
confidence: 90%
“…Furthermore, given the elevated CXCL13 expression in the serum of patients with metastatic disease as compared with patients without evidence of tumour burden, this chemokine may also serve as a tumour marker. In our analysis of breast cancer cell lines and tumour samples, we found the expression of chemokine receptor CXCR5 to be restricted to the cytoplasma, a finding that is in line with observations of Muller et al (2006) who detected CXCR5 intracellulary but did not detect surface expression of CXCR5 in cell lines and tumour samples from patients with metastatic head and neck cancer. Although these findings, at first glance, do not support the concept of CXCR5 as the main target for CXCL13 overexpression in breast cancer, we believe that they do not reflect the potential role this chemokine receptor might play in vivo.…”
Section: Discussionsupporting
confidence: 90%
“…A growing number of studies have confirmed that CXCR4 is expressed on the surface of a variety of tumor cells (such as salivary adenoid cystic carcinoma, breast cancer, and oral squamous carcinoma cells). It interacts with its corresponding chemokines, including CXCL12, and the molecular pair then influences the biological behavior of tumor cells (Muller et al, 2006;Kato et al, 2003;Almofti et al, 2004). We found here that, although pancreatic cancer cells do not themselves express CXCL12, they do express CXCR4 which was confirmed by immunoblotting mehhod (Grzesiak et al 2007); therefore, these cells are capable of responding to chemotactic signals from CXCL12.…”
Section: Discussionsupporting
confidence: 56%
“…Molecular crosstalk between the primary tumor and the pre-metastasis niche through secreted stimulatory signals helps govern the homing of mCSCs. Trafficking towards preferred tissues and organs of mCSCs is guided by cues such as oxygen gradients or other chemo-attractants derived from niche sites [94,[123][124][125].…”
Section: Cscs and Metastasismentioning
confidence: 99%